ASSOCIATION BETWEEN EATING PERFORMANCE, AND DENTAL RELATED FUNCTION AND ORAL HEALTH IN RESIDENTS WITH DEMENTIA. (11th November 2018) - Liu, W; Shaw, C; Chen, X
Abstract: Background: Despite the physiologic relationship, there is lack of evidence on how dental related function and oral health impact eating performance in this population. The aim is to examine the association of eating performance with dental related function and oral health among cognitively impaired residents in residential care facilities. Materials and methods: A secondary analysis was performed using observational data collected from an instrument development study that psychometrically tested the Dental Activities Test for measuring dentally related. Participants included 90 residents with normal to severely-impaired cognition from three assisted living facilities in North Carolina. Multilevel mixed-effects ordered logistic models were used to examine the relationship between eating performance, and dental related function and oral health. The dependent variable was eating performance measured by the single "eating" item (scored from 0 to 4 on level of dependence). The independent variables were resident age, gender, dental related function, and oral health. Results: The resident and facility clustering effects accounted for 88% of variance in eating performance, among which 84% was explained by dental related function and oral health. Eating performance was associated with dental related function (coefficient = -.10, 95%CI = -.19, -.01, P = .025), and was not associated with other characteristics. As dental related function increased, eating performance improved. Conclusion: Eating performance is influenced by the complex relationship with dental related function and oral health in assisted living residents. Novel interventions using interdisciplinary partnerships are needed to maintain dental related function and oral health to optimize eating performance.